Bodies, technologies and methods - Jones, Phil (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book examines how different technologies can be used to enhance research methods in the social sciences and humanities. The boundary between the body and the digital has become increasingly blurred in recent years due to the rise of technologies that capture and reshape our embodied selves. New technologies all too often reflect the attitudes of the privileged white men who dominate the tech sector. This book thus, in part, considers how critical researchers can employ new technologies while challenging some of the problematic assumptions that underpin their design. It also includes a series of case studies that examine the dynamic use of different techniques to explore key questions around the intersection of embodiment and the digital. With a playful, experimental approach to conducting research today, this book offers new, cutting-edge methods that respond to the potential of different technologies. It will be invaluable reading for undergraduate and post-graduate students of social sciences and humanities to explore ways in which this approach can bring new insights to a range of interdisciplinary research questions"--
Introduction: playing with methods -- Privacy, transparency and ethical research methods -- Measuring the body -- Gaming & virtual landscape -- Creative practice -- Maps, apps and mobilities -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Technological innovations -- Social aspects; Technological innovations -- Research -- Methodology; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography